A239 CLINICAL MANAGEMENT OF COLORECTAL POLYPS: RESULTS OF AN INTERNATIONAL SURVEY. (15th March 2019) - Willems, P; Orkut, S; Ditisheim, S; Bouin, M; Faulques, B; Pohl, H; von Renteln, D
Abstract: Background: Endoscopic management of colorectal polyps continues to evolve. Alternatives to histopathology assessment for diminutive polyps such as the resect-and-discard strategy have been introduced while polypectomy guidelines have incorporated changes toward using electrocautery free techniques. Aims: We conducted an international survey to better understand current uptake and barriers of these polyp management techniques. Methods: A survey questionnaire was distributed through endoscopy, gastroenterology and surgical societies worldwide to colonoscopy practitioners. Study domains included physicians practice characteristics, perception of cancer risk in diminutive polyps, utilization and potential concerns with the resect-and-discard strategy, utilized polypectomy techniques and changes in practice patterns in recent years. Results: 808 practitioners participated in the survey. 48.4 % (95% CI 45.0%-51.9%) of participants believe that leaving diminutive polyps in place will increase the cancer risk for patients and 54.7 % (95% CI 53.6%-60.4%) believe that the current CT-colonoscopy practice, which ignores diminutive polyps, are probably or definitely increasing patients risk of cancer. 80.3% (95% CI 77.5%-83.0%) of responders believe that using the resect-and-discard strategy for diminutive polyps will not increasing cancer risk, however 84.2% (95% CI 81.6%-86.7%) are presently not using it and 59.9% (95% CI 56.5%-63.2%) do not believe that it is feasible for use in general practice. Potential medico-legal issues and being afraid of giving wrong surveillance intervals based on optical diagnosis were the most common barriers for implementation. In regard to polypectomy techniques, 87.5 % (95% CI 85.2%-89.8%) of responders reported an increased use of cold snare polypectomy in the past 5 years, with 55.3% (95% CI 51.9%- 58.7%) reporting more than a 50% increase. Cold snare polypectomy is the most frequently used resection technique for 4 to 5 mm and 6 to 10 mm polyps: 67.0% (95% CI (63.7%-70.2%) and 55.2% (95% CI 51.8%-58.6%) respectively. Conclusions: The majority of endoscopists has concerns that leaving diminutive polyps unresected is associated with an increased risk of cancer and also believe that the resect-and-discard strategy, in its current form, is not feasible for widespread clinical implementation. With regard to polypectomy techniques, there has been a marked increase in the last 5 years using cold snare polypectomy to resect 4 to 10 mm polyps. Funding Agencies: None